Capillary effects on flax fibers – Modification and characterization of the wetting dynamics. (October 2015) - Pucci, Monica Francesca; Liotier, Pierre-Jacques; Drapier, Sylvain
Abstract: Introducing bio-based composites has now become an opportunity of development for industry. Accordingly, Liquid Composite Moulding ( LCM ) processes are increasingly used for manufacturing those composites, mainly in the transportation industry, since they are considered as effective and low cost routes to manufacture bio-based composites fitting high quality requirements, even for parts with complex shape. However observations of a large amount of voids in bio-based composites call for an improved understanding of the local wetting phenomena that occur during impregnation of the natural reinforcements. The purpose of the present work is to study the influence of flax fiber surface chemistry on the local wetting dynamics. Flax reinforcements were submitted to a thermal treatment to modify the chemical composition of fiber surface. In order to analyze the fiber's wetting behavior, some methods for measuring apparent static contact angles and surface energy were firstly validated on solids of defined geometry, and subsequently applied to untreated and treated flax fibers. The Owens–Wendt's approach was used to determine both components of apparent surface energy, indicating polar and dispersive interactions in materials. Subsequently dynamic tests were carried out on both types of chopped flax fibers in order to evaluate apparent advancing dynamic contact angles. Considerations about morphological effects have also been included. Finally bio-based composite plates reinforced with untreated and treated flax quasi-UD were simultaneously fabricated by LCM process, and observation of the porosities highlighted some benefits of using treated flax fibers.